Oxford think! new syllabus Mathematics 1 (workbook) (Karachi : Oxford universiy press, 2024)
"Think! New Syllabus Mathematics 1 Workbook (8th Edition)" is a companion workbook designed to help middle school students practice and reinforce the concepts introduced in the Think! New Syllabus Mathematics 1 textbook. It provides a wide range of exercises to support the learning process and enhance students' mathematical skills.
Keywords: Math : Workbook; Oxford :8th edition